HOMA-S is Associated with Greater HbA1c Reduction with a GLP-1 Analogue in Patients with Type 2 Diabetes - Heald, A. H.; Narayanan, R. P.; Lowes, D.; Jarman, E.; Onyekwelu, E.; Qureshi, Z.; Laing, I.; Anderson, S. G. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Exenatide, a glucagon-like peptide-1 (GLP-1) analogue, is an effective glucoregulator for treating overweight individuals, not at target HbA1 c. This prospective study aimed to determine whether estimates of beta cell function (HOMA-B) and insulin sensitivity (HOMA-S) predict response to Exenatide treatment.Prospective data on 43 type 2 diabetes patients were collected for up to 2.8 years in UK primary care. HOMA-B and HOMA-S were estimated prior to initiating Exenatide, with monitoring of cardio-metabolic risk factors.Mean (SD) age and BMI pre-treatment were 54.1±10.5 years and 35.7±7.5 kg/m2 respectively. HbA1c decreased (mean reduction 0.9%, p=0.04; p for trend=0.01) in 61% of patients. In univariate analyses, HOMA-S as a measure of insulin sensitivity was inversely (β=− 0.41, p 0.009) related to change in HbA1c, with no relation for HOMA-B.In a random effects regression model that included age at baseline, weight, LDL-C, HDL-C and triglycerides, change in HbA1c (β= − 0.14, p<0.001) and HDL-C (β= − 0.52, p=0.011) were independently associated with increasing insulin sensitivity (r2=0.52). Thus patients with greater measured insulin sensitivity achieved greater reduction in HbA1c independent of the factors described above.In logistic regression those in the highest tertile of log-HOMA-S were 45% more likely to have a fall in HbA1c with an odds ratio (OR) of 0.55 (95% CI 0.47–0.66) p<0.0001 (log likelihood ratio for the model χ2=71.6, p<0.0001).Patients with greater measured insulin sensitivity achieve greater reduction in HbA1c with Exenatide. Determination of insulin sensitivity may assist in guiding outcome expectation in overweight patients treated with GLP-1 analogues.
Keywords: HOMA; type 2 diabetes; GLP-1 analogue; HbA1c